Sustainable Management: A Bibliometric Mapping of Global Trends and Thematic Shifts - Loso Judijanto; Tati Handayani (West Science Business and Management, 2026)
This study aims to map the global development and thematic evolution of sustainable management research using a bibliometric approach. Data were collected from the Scopus database and analyzed using VOSviewer to examine publication trends, keyword co-occurrence, and the intellectual structure of the field. The results indicate that sustainable development serves as the central theme, supported by dominant topics such as environmental management, environmental impact, and resource efficiency. The analysis also identifies several major research clusters, including circular economy, carbon management, water and waste management, and technology-driven sustainability through artificial intelligence and machine learning. Furthermore, the findings reveal a clear thematic shift from traditional environmental concerns toward more integrated, interdisciplinary approaches that incorporate digital innovation and sector-specific applications. The study highlights the increasing role of technological advancement and regional contributions in shaping sustainable management research. Despite significant progress, gaps remain in the integration of social and governance dimensions, suggesting opportunities for future research to develop more comprehensive and holistic sustainability frameworks. This study contributes to the literature by providing an integrative overview of the intellectual landscape and emerging directions in sustainable management research.